(untitled) (Experimental biology, 2009)
The aim of this study was to investigate the structure of the goat adrenal cortex. For this purpose, thirty sixadrenals were collected from adult goats. The tissues were processed for both light and electron microscopy. The adrenal cortex is composed of three distinct zones. The outer zone is the zona glomerulosa and its cells arranged in glomerules. The zona fasciculata is the thickest zone and is composed of columns of secretory cells separated by prominent capillaries. The cells are polygonal and have many intracellular lipid droplets. The zona reticularis is also composed of polygonal cells, whose arrangement is less linear and more as round nests or clumps of cells. Ultrastructuraly: zona glomerulosa are characterized by prominent mitochondria with tubular cristae, zona fasciculata have many cytoplasmic lipid droplets, mitochondria with vesicular cristae, and abundant smooth endoplasmic reticulum. The zona reticularis is distinguished; by the presence of prominent lysosomes in the cytoplasm.